#TITLE_ALTERNATIVE# - PUTRI MURBEKTI (NIM : 12213078), ANDRA
Abstract Artificial lift methods are used for reservoir that are no longer able to produce naturally. Few design studies and production optimization using ESPÃ‚Â’s as a lifting method in the area of heavy oil have been published. Gas content in fluid production will affect the working ability of the submersible pump. The presence of gas will have a major effect on percentage of gas entering the pump which associated to ESP design process. Production simulation for natural flow well in this study will be used to determine time to install ESP. Percentage of pump inlet gas calculation for three types of intake will affect the design of ESP. The efficient ESP design will be used for production simulation to understand the effect of ESP installation based on production profile. The separation ability of intake will affect production ability of well with ESP. Certain degree of separation ability will stop the fluid production from well due to high friction loss in fluid flow. Efficient selection of pump, motor, and ESP cable will be seen based on match curve of pressure calculation from bottom hole to surface and surface to bottom hole. This study will be useful to confirm the ability of ESP as an alternative lifting method for heavy oil well with relatively high GOR.